Diffuse large B-cell lymphoma that develops after adalimumab using adalimumab in a patient with psoriasis - Esra Yıldırım Bay; Elif Moustafa; İlteris Oğuz Topal; Özben Yalçın; Naciye Demirel (Galenos Publishing House, 2021)
Psoriasis is a polygenic, systemic inflammatory disease seen in 2% to 3% of the population and leads to a serious deterioration in the quality of life. As a result, studies on the pathophysiology of this disease have led to the development of cytokine-targeted therapies, especially the widespread use of treatments targeting tumor necrosis factor-alpha (TNF-α). The role of TNF-α in inflammation and important physiological pathways has increased safety concerns. In the literature, it has been reported that infections, cardiac failure, neurological diseases, and malignancies may develop related to the use of anti-TNF-α agents. In this case report, a 59-year-old male patient was started on adalimumab as a biological agent for erythrodermic psoriasis. Twenty-four months after starting biological agent therapy, hard nodules occurred under his skin in both the inguinal and axillary regions. The patient was diagnosed with diffuse large B-cell lymphoma based on his histopathological and laboratory examinations. This case report aims to discuss the specific malignancies that may develop from anti-TNF-α agents and the potential pathophysiological mechanisms suggested in the current literature.